Catalyzing development a new vision for aid - Kharas, Homi J. 1954-; Jung, Woojin; Makino, Koji (Brookings Institution Press, 2011)
"Provides analysis of how the field of international aid is changing with new approaches necessary because of new actors providing assistance, including middle-income countries, private philanthropists, and the private sector, and new challenges, including climate change and the large number of fragile states"--Provided by publisher.